TEACHING OF INFORMATICS AND INFORMATION TECHNOLOGY LESSONS ON THE BASIS OF THE 4 "K" MODEL - Xakimova Yoqutxon Toxirjon qizi (Western European Studies, 2024)
The article examines the issues of improving the quality of education, modern education, how a modern teacher should teach a student today, 4 "K" skills, effective use of modern methods in lessons
Keywords: modern teacher; 4; methods